A New Strategy to Investigate the Efficacy Markers Underlying the Medicinal Potentials of Orthosiphon stamineus Benth. - Li, Zheng; Qu, Biao; Zhou, Lei; Chen, Hongwei; Wang, Jue; Zhang, Wei; Chen, Caifa (Frontiers in Pharmacology, 2021)
Orthosiphon stamineus Benth. (OSB) is a well-known herbal medicine exerting various pharmacological effects and medicinal potentials. Owing to the complex of phytochemical constituents, as well as the ambiguous relationship between phytochemical constituents and varied bioactivities, it is a great challenge to explore which constituents make core contribution to the efficacy of OSB, making it difficult to determine the efficacy makers underlying the varied efficacies of OSB. In our work, a new strategy was exploited and applied for investigating efficacy markers of OSB consisting of phytochemical analysis, in vivo absorption analysis, bioactive compound screening and bioactive compound quantification. Using liquid chromatography coupled with mass spectrometry, a total of 34 phytochemical components were detected in OSB extract. Subsequently, based on in vivo absorption analysis, 14 phytochemical constituents in the form of prototypes were retained as potential bioactive compounds. Ten diseases were selected as the potential indications of OSB based on previous reports, and then the overall interaction between compounds, action targets, action pathways and diseases was revealed based on bioinformatic analysis. After refining key pathways and targets, the interaction reversing from pathways, targets to constituents was deduced, and the core constituents including tanshinone IIA, sinensetin, salvianolic acid B, rosmarinic acid and salvigenin, were screened out as the efficacy markers of OSB. Finally, the contents of these five constituents were quantified in three different batches of OSB extracts. Among them, the content of salvianolic acid B was the highest while the content of tanshinone IIA was the lowest. Our work could provide promising direction for future research on the quality control and pharmacological mechanism of OSB.